Chemistry, Biosynthesis and Pharmacology of Streptonigrin: An Old Molecule with Future Prospects for New Drug Design, Development and Therapy - Nabihah Nasir N; Sekar M; Ravi S; Wong LS; Sisinthy SP; Gan SH; Subramaniyan V; Chidambaram K; Mat Rani NNI; Begum MY; Ramar M; Safi SZ; et al. (Drug Design, Development and Therapy, 2023)
Naurah Nabihah Nasir,1 Mahendran Sekar,2,3 Subban Ravi,4 Ling Shing Wong,5 Sreenivas Patro Sisinthy,6 Siew Hua Gan,2 Vetriselvan Subramaniyan,7 Kumarappan Chidambaram,8 Nur Najihah Izzati Mat Rani,6 M Yasmin Begum,9 Mohankumar Ramar,10 Sher Zaman Safi,11 Siddharthan Selvaraj,12 Senthil Kumar Chinna Maruthu,13 Shivkanya Fuloria,14 Neeraj Kumar Fuloria,14 Pei Teng Lum,1 Sinouvassane Djearamane15 1Department of Pharmaceutical Chemistry, Faculty of Pharmacy and Health Sciences, Royal College of Medicine Perak, Universiti Kuala Lumpur, Ipoh, Perak, 30450, Malaysia; 2School of Pharmacy, Monash University Malaysia, Bandar Sunway, Selangor, 47500, Malaysia; 3Center for Transdisciplinary Research, Department of Pharmacology, Saveetha Institute of Medical and Technical Sciences, Saveetha Dental College and Hospital, Saveetha University, Chennai, Tamil Nadu, 600077, India; 4Department of Chemistry, Karpagam Academy of Higher Education, Coimbatore, Tamil Nadu, 641021, India; 5Faculty of Health and Life Sciences, INTI International University, Nilai, 71800, Malaysia; 6Faculty of Pharmacy and Health Sciences, Royal College of Medicine Perak, Universiti Kuala Lumpur, Ipoh, Perak, 30450, Malaysia; 7Jeffrey Cheah School of Medicine and Health Sciences, Monash University Malaysia, Bandar Sunway, Subang Jaya, Selangor, Malaysia; 8Department of Pharmacology, College of Pharmacy, King Khalid University, Abha, 62529, Saudi Arabia; 9Department of Pharmaceutics, College of Pharmacy, King Khalid University, Abha, 61421, Saudi Arabia; 10Department of Surgical Research, Rhode Island Hospital, Alpert Medical School, Brown University, Providence, RI, 02903, USA; 11Faculty of Medicine, Bioscience and Nursing, MAHSA University, Jenjarom, Selangor, 42610, Malaysia; 12Faculty of Dentistry, AIMST University, Bedong, Kedah, 08100, Malaysia; 13Department of Pharmacology, Karpagam College of Pharmacy, Coimbatore, Tamilnadu, 641032, India; 14Faculty of Pharmacy, AIMST University, Bedong, Kedah, 08100, Malaysia; 15Department of Biomedical Science, Faculty of Science, Universiti Tunku Abdul Rahman, Kampar, Perak, 31900, MalaysiaCorrespondence: Ling Shing Wong, Faculty of Health and Life Sciences, INTI International University, Nilai, 71800, Malaysia, Tel +6014 – 3034057, Email lingshing.wong@newinti.edu.my Sinouvassane Djearamane, Department of Biomedical Science, Faculty of Science, Universiti Tunku Abdul Rahman, Kampar, 31900, Perak, Malaysia, Tel +6016 – 4037685, Email biochsinouvas07@gmail.comAbstract: Streptonigrin is an aminoquinone alkaloid isolated from Streptomyces flocculus and is gaining attention as a drug molecule owing to its potential antitumor and antibiotic effects. It was previously used as an anticancer drug but has been discontinued because of its toxic effects. However, according to the most recent studies, the toxicity of streptonigrin and its structurally modified derivatives has been reduced while maintaining their potential pharmacological action at lower concentrations. To date, many investigations have been conducted on this molecule and its derivatives to determine the most effective molecule with low toxicity to enable new drug discovery. Therefore, the main objective of this study is to provide a comprehensive review and to discuss the prospects for streptonigrin and its derived compounds, which may boost the molecule as a highly interesting target molecule for new drug design, development and therapy. To complete this review, relevant literature was collected from several scientific databases, including Google Scholar, PubMed, Scopus and ScienceDirect. Following a complete screening, the obtained information is summarized in the present review to provide a good reference and accelerate the development and utilization of streptonigrin and its derivatives as pharmaceuticals.Graphical Abstract: Keywords: streptonigrin, chemistry, biosynthesis, pharmacology, anticancer, antibacterial